Characteristic investigation of a flow-dependent inertia hydraulic converter driven by an equivalent fast switching valve. (April 2022) - Chen, Xiaoming; Zhu, Yuchuan; Wiens, Travis; Bitner, Doug; Ling, Jie
To acquire a linear load pressure with the potential of energy-saving compared with conventional throttling hydraulic systems, a switched hydraulic circuit (referred to as a flow-dependent inertia hydraulic converter) featuring a flow-dependent inertial effect was proposed. In this device, the flowing fluid modulated by an equivalent fast switching valve allows the fluid inertance at the connection pipe and rotation inertia incorporated in the flywheel to be combined. The theoretical and simulation models of the flow-dependent inertia hydraulic converter were established, and then the flow-dependent inertia was discussed and quantified. The predictions of the load pressure, flywheel speed and system efficiency were confirmed by experimental measurements. Results indicated that the theoretical and simulation predictions match well with the experiments for this configuration. The pressure wave propagation effect within the connection pipe is responsible for the variation in the transient load pressure and flywheel speed that is initially modulated by the rotation inertia theoretically, which seriously questions the predecessor's hypothesis of using a compressible volume to model the upstream connection pipe. The parabolic mean suction flow induced by the flow-dependent inertia draw our attention to the available supply flowrate and duty cycle. Finally, the throttling loss and system efficiency that varies with the desired characteristics is superior to that of conventional throttling hydraulic systems theoretically, and an acceptable system efficiency was obtained under the premise of ignoring friction experimentally.